Utilization of community resources by General Science teachers of high schools in Iloilo City and its suburbs - Cordero, Josefina A. 1931- (s.n.], 1960)
The writer of this study aims to survey the community resources in Iloilo City and its suburbs, which have direct implications upon general science courses offered in the high school curriculum.